Designing a Medical Records Student Lab Learning Application for Patient Data Management - Niska Salsiani Sinta; Sri Wahyuni; Abdul Adam Mansyur; Rini Alia Wicaksono (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Electronic medical records (EMR) are mandatory in Indonesian health facilities, yet students often lack access to systems mirroring real-world community health center (Puskesmas) workflows. This study developed SIMETRIK, a simulation-based tool designed to bridge the gap between classroom theory and clinical competency. Using a Research and Development (R&D) approach, the application was built via a waterfall model incorporating needs analysis, UML-based design, and high-fidelity prototyping. Evaluation involved 15 respondents, 10 students, 4 lecturers, and 1 practitioner, who assessed the system using a 1–4 Likert scale across five dimensions: ease of use, navigation clarity, feature alignment, learning utility, and satisfaction. Results indicated that user satisfaction earned the highest mean score (M = 3.33), followed by the application’s utility as a learning medium (M = 3.00). Feature alignment with public health workflows was rated at 2.67. Conversely, ease of use and navigation clarity received lower scores (2.33 and 2.13, respectively), signaling a requirement for interface refinement. Despite navigational hurdles, participants successfully executed registration and clinical documentation tasks. Feedback confirmed that SIMETRIK significantly improved students' understanding of EMR processes and aligned with professional practice requirements. These findings demonstrate that the application serves as a viable simulation platform for laboratory learning, underscores the importance of competency-focused digital tools, and establishes a foundation for future database-driven implementations in health informatics education Keywords: SIMETRIK, Electronic Medical Records, Simulation-Based Learning, Usability Evaluation, Patient Data Management, Competency-Based Education